The Effect of Maze Media on teh Ability to Recognize Numbers 1-20 in 5-6 Year-Old Children. - Ainnun Ibrahim Hamid; Yeni Rachmawati; Badru Zaman (Aulad: Journal on Early Childhood, 2026)
Early childhood numeracy is a fundamental ability that supports later mathematical learning, yet many children still experience difficulties in recognizing numbers. This study aims to examine the effect of labyrinth (maze) learning media on the number recognition ability of children aged 5–6 years. The research employed a quantitative pre-experimental method involving 12 children in group B selected through purposive sampling. Data were collected using observation sheets measuring children’s ability to recognize numbers 1–20. Data analysis was conducted using the non-parametric Wilcoxon Signed Rank Test. The results showed an Asymp. Sig. (2-tailed) value of 0.002 (p < 0.05), indicating a significant effect of labyrinth media on children’s number recognition ability. These findings imply that labyrinth media can be an effective and engaging learning tool to enhance early childhood numeracy skills in early education settings